The use of broad-range bacterial PCR in the diagnosis of infectious diseases: a prospective cohort study. (June 2019) - Tkadlec, J.; Peckova, M.; Sramkova, L.; Rohn, V.; Jahoda, D.; Raszka, D.; Berousek, J.; Mosna, F.; Vymazal, T.; Kvapil, M.; Drevinek, P.
Abstract: Objectives: Broad-range PCR has the potential to detect virtually any bacterial species via amplification and nucleotide sequencing of a DNA region common to all bacteria. We aimed to evaluate its usefulness and clinical relevance when applied to a wide variety of primary sterile materials. Methods: A prospective study including 1370 samples (75 heart valves, 151 joint tissue samples, 230 joint aspirates, 848 whole blood samples and 66 culture-negative cerebrospinal fluid samples) were studied by using a commercial PCR system for detecting 16S rDNA (Molzym). The PCR results were compared with culture and were considered to provide added diagnostic value only if the PCR approach revealed new pathogens that were missed by culture. Results: The added value of PCR was evident in 173 of 555 PCR-positive samples (0.126; 0.109–0.144 (proportion from all tested samples; 95% confidence interval)), most frequently in examinations of heart valves (0.56; 0.448–0.672) and joint tissue samples (0.219; 0.153–0.284). In contrast, the lowest rate of PCR with added value was noted for blood samples, regardless of the patient cohort they had been drawn from (nononcologic patients from intensive care: 0.065; 0.043–0.087, haematooncologic children: 0.048; 0.027–0.070). Moreover, PCR missed up to 7.1% of blood culture findings (0.071; 0.048–0.095) regarded as clinically relevant, which was the second highest failure rate after joint tissue samples (0.099; 0.052–0.147). Conclusions: Broad-range PCR substantially increases detection rate of pathogens, especially from heart valves and joint samples. However, a concurrent risk of false-negative PCR results justifies the need for parallel culture.